Pneumomediastinum and pneumoretroperitoneum: an extremely rare presentation of acute appendicitis. (9th January 2015) - Dalbem, Caroline Sauter; Nunes, Thiago Franchi; Machado, Magali da Silva Sanches; Goldman, Suzan Menasce
Abstract : A 22-year-old woman presented with abdominal pain for 12 days. On examination, the abdomen was slightly distended and painful to palpation in the right flank. Subsequent abdominal imaging showed inflammation in the right iliac fossa, retroperitoneal air pockets with inflammation, and signs of pneumomediastinum. Exploratory laparotomy revealed a perforated retrocaecal appendix with abscess extending to the retroperitoneum. Surgical intervention involved a right hemicolectomy followed by end-to-side anastomosis of the ileum to the transverse colon. Histopathological examination of the resected specimen revealed intense inflammation of the caecum and no signs of malignancy. The patient was discharged in good condition 54 days after surgery.